Diluting ferric carboxymaltose in sodium chloride infusion solution (0.9% w/v) in polypropylene bottles and bags: effects on chemical stability - Philipp, Erik (Eur J Hosp Pharm, 2016)
OBJECTIVES: This study was designed to assess the physicochemical stability of colloidal ferric carboxymaltose solution (Ferinject) when diluted and stored in polypropylene (PP) bottles and bags for infusion. METHODS: Two batches of ferric carboxymaltose solution (Ferinject) were diluted (500 mg, 200 mg and 100 mg iron in 100 mL saline) in PP bottles or bags under aseptic conditions. The diluted solutions were stored at 30°C and 75%±5% relative humidity (rH) for 72 h, and samples were withdrawn aseptically at preparation and after 24 h, 48 h and 72 h. Multiple parameters were used to test stability-related measures (pH, total iron and iron (II) content, molecular weight range determination, microbial contamination and particles count ≥10 μm). RESULTS: Overall, Ferinject diluted in 0.9% (w/v) NaCl solution and stored in PP bottles and bags was stable within the specifications for the complex and the acceptability limits set for all assays. In both containers, total iron content remained stable, within 10% of the theoretical iron content, and levels of iron (II) remained far below the threshold of acceptability. All preparations were free from sediments, particle numbers were acceptable and there was no microbial contamination. The molecular weight distribution and polydispersity index were also acceptable. CONCLUSIONS: Under the tested experimental conditions, colloidal ferric carboxymaltose solution (Ferinject) diluted in saline in PP infusion bottles or bags demonstrated physical and chemical stability for up to 72 h at 30°C and 75% rH. Because of the lack of additional clinical data, when using ferric carboxymaltose, physicians/pharmacists should refer to the dilution and storing recommendations given in the product's summary of product characteristics.